Kleine-Levin syndrome: a case report - Tiwari, Anshuman; Agarwal, Anju; Bharti, Shantanu; Kohli, Ajay (International Journal of Advances in Medicine, 2017)
Kleine-Levin syndrome is characterized as a periodic hypersomnia crisis as well as dietary and variable significant psychiatric symptoms. This case report is of 15 year boy who presented with characterstic features of hypersomnia, hyperphagia, affective features like irritability and cognitive disturbances in an episodic manner with spontaneous remission. Due to the above clinical presentation we made the diagnosis of Kleine-Levin syndrome in this patient who was started on psychostimulant and responded well on these medications.